Gambaran kadar besi darah pada pekerja bangunan - Laluyan, Rebecca E.; Assa, Youla A.; Paruntu, Michaela E. (e-Biomedik, 2016)
Abstract: Micronutrients such as iron have an important roles in human body. Vigorous activity could lead to change in iron levels, whether to be high or to be low. The purpose of this study was to determine the iron levels in construction workers. The study was conducted in a descriptive cross sectional arrangement. Thirty respondents who were eligible to the inclusion criteria. Samples were taken using a total sampling methods. The results showed that 27 respondent (90%) with a normal iron levels of 30-400 ng/mL, 2 respondent (6.67%) with high iron levels, and 1 respondent (3.33%) with low iron levels.Conclusion: Most of the iron levels in construction workers are in a normal limit.Keywords: Iron levels, construction workers, vigorous activityÂ Abstrak: Mikronutrien seperti besi sangat bermanfaat bagi tubuh manusia. Pada aktivitas fisik terutama dengan intensitas berat dapat menyebabkan kadar besi berubah, antara menjadi tinggi atau menjadi rendah. Tujuan dari penelitian ini adalah untuk mengetahui gambaran kadar besi pada pekerja bangunan. Penelitian yang digunakan bersifat deskriptif dengan pendekatan cross sectional study.Sampel dalam penelitian ini berjumlah 30 orang yang sesuai kriteria inklusi dan bersedia menjadi responden. Metode pemilihan sampel menggunakan cara total sampling. Hasil penelitian didapatkan responden yang memiliki kadar besi normal sesuai rujukan antara 30-400 ng/mL terdapat sebanyak 27 orang (90%), 2 orang (6.67%) dengan kadar besi yang lebih dari nilai normal, dan 1 orang (3.33%) dengan kadar besi yang kurang dari normal. Simpulan: Gambaran kadar besi pada pekerja bangunan sebagian besar dalam batas normal. Kata kunci: kadar besi, pekerja bangunan, aktivitas intensitas berat.